Traces of glaciation in the NW mountains of Portugal: overview of current knowledge and prospects of research - Vieira, António (2015)
The study of Pleistocene glaciation in the Northwest of Portugal has interested the scientific community since the late nineteenth century. From all mountains of Minho, only the Peneda and Geres are consensually regarded as mountain areas affected by Quaternary glaciations, although other mountainous areas appear to show identical effects of glaciation. Thus, this paper presents a synthesis of current knowledge and research perspectives of the remains of the glaciers in the mountains NW Portugal.